2016
DOI: 10.1165/rcmb.2015-0261oc
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Cell–Derived Secreted and Transmembrane 1a Signals to Activated Neutrophils during Pneumococcal Pneumonia

Abstract: Airway epithelial cell responses are critical to the outcome of lung infection. In this study, we aimed to identify unique contributions of epithelial cells during lung infection. To differentiate genes induced selectively in epithelial cells during pneumonia, we compared genome-wide expression profiles from three sorted cell populations: epithelial cells from uninfected mouse lungs, epithelial cells from mouse lungs with pneumococcal pneumonia, and nonepithelial cells from those same infected lungs. Of 1,166 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 51 publications
(81 reference statements)
0
35
0
Order By: Relevance
“…These studies have revealed a more complex population of lung epithelial cells than had been previously appreciated (2). A recent study from our group revealed the unanticipated finding that epithelial cells from lungs with bacterial pneumonia exhibited higher expression of the mRNA encoding the Piwi protein MIWI2 during pneumococcal pneumonia (3).…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…These studies have revealed a more complex population of lung epithelial cells than had been previously appreciated (2). A recent study from our group revealed the unanticipated finding that epithelial cells from lungs with bacterial pneumonia exhibited higher expression of the mRNA encoding the Piwi protein MIWI2 during pneumococcal pneumonia (3).…”
Section: Introductionmentioning
confidence: 84%
“…Specific cell sources of Miwi2 expression were interrogated in mice infected with S. pneumoniae using a previously described protocol for isolating purified cell populations recovered from whole lung enzymatic digests and bronchoalveolar lavage fluid (3,16 ized in the cytoplasm, and restricted to airway cells ( Figure 1E). To determine whether the increase in Miwi2 mRNA correlated with increased MIWI2 protein expression, tissue sections isolated from uninfected or infected lungs were quantitatively compared, and demonstrated that the number of MIWI2-positive cells was significantly increased as a result of infection ( Figure 1F).…”
Section: Miwi2 Is Expressed In Adult Lungs and Induced During Pneumocmentioning
confidence: 99%
See 1 more Smart Citation
“…A protective action observed was the induction of CXCL5 by epithelial cells (10), advancing prior studies that suggested this was an epithelial-specific product during pneumonia that elicits neutrophil recruitment (12, 13). Transcriptional profiling experiments in mice with pneumococcal pneumonia have now revealed that CXCL5 is only one of many hundreds of genes that are induced preferentially in epithelial cells during infection, dozens of which are secreted products like CXCL5 that can mediate immune cell cross-talk (14). Another epithelial-specific product was identified as a neutrophil activator, secreted and transmembrane 1 (Sectm1), which stimulates recruited neutrophils to make more of the neutrophil-attracting chemokine, CXCL2, thereby amplifying the positive feedback of inflammation within the infected lung (14).…”
Section: Advances In Immune Resistancementioning
confidence: 99%
“…Transcriptional profiling experiments in mice with pneumococcal pneumonia have now revealed that CXCL5 is only one of many hundreds of genes that are induced preferentially in epithelial cells during infection, dozens of which are secreted products like CXCL5 that can mediate immune cell cross-talk (14). Another epithelial-specific product was identified as a neutrophil activator, secreted and transmembrane 1 (Sectm1), which stimulates recruited neutrophils to make more of the neutrophil-attracting chemokine, CXCL2, thereby amplifying the positive feedback of inflammation within the infected lung (14). Harnessing the power of epithelial innate immunity, pharmacologically triggering these cells is being pursued as a means to provide protection against diverse respiratory infections (15), and it now appears that this can be effective even in mice modeling leukemia patients, despite profound immune dysregulation due to both leukemia and leukemia treatment (16).…”
Section: Advances In Immune Resistancementioning
confidence: 99%